A SIMPLIFIED STATISTICAL TECHNIQUE FOR USE IN VERIFYING ACCOUNTS RECEIVABLE. - Ridilla, Richard A. (The Accounting Review, 1959)
In an attempt to promote more general familiarity with statistical approaches to testing accounts receivable, the article is designed to reduce to a minimum the statistical background necessary for an understanding of an application of statistical sampling and to substitute prepared tables for terms and formulas so that the accountant need use only basic mathematical processes. The purpose of an audit of accounts receivable or any other asset is to prove to the auditor's satisfaction the existence, ownership, valuation, accuracy of record and fairness of presentation of the account. The auditor usually witnesses the physical existence of the asset, at least on a test basis. Ownership by the client at financial statement date must also be carefully determined and valuation should be in accordance with generally accepted accounting principles consistently applied. Any inaccuracies in the records are noted, corrected if material, and brought to the attention of management which has primary responsibility for the accounting records.